Managing Excellent Class Programs In Increasing Learning Achievement - Sri Nuri Rahmawati (Mapendis: Jurnal Manajemen Pendidikan Islam, 2023)
The world of education is entering this global era with all its advantages and challenges. With a positive response, it will implement tight competition between schools and trigger creative efforts by education administrators to improve the quality of their schools. In general, madrasas as Islamic educational institutions lose out in this global competition. In conditions of intense competition like this, the role of a strong image will be increasingly important for service providers in winning the competition. It is in this context that Islamic education institutions carry out strategies to improve the image of madrasas, one of which is with a superior class program. This researcher aims to analyze the superior class program management in improving student achievement. This researcher uses a qualitative approach with data collection procedures using interviews, observation and documentation. Based on the process of data collection and data analysis, the researchers produced superior class program management in improving student achievement at MAN 1 Wonosobo , namely planning including concepts, input processes, infrastructure and data sources; organizing includes the organizational structure: implementation includes the recruitment of teaching staff, the learning process and the curriculum used; evaluation includes evaluation of learning, achievements obtained by students and their output.